Colat alius Deum, alius Iovem: Tertulijan, verska svoboda (libertas religionis) in verski pluralizem = Colat alius Deum, alius Iovem: Tertullian, Freedom of Religion (libertas religionis) and Religious Pluralism - Bogataj, Jan Dominik (Edinost in dialog, 2022)
This paper analyses Tertullian’s innovative syntagm "religious freedom" (libertas religionis) from several perspectives, presenting the historical and literary context that enabled the Carthaginian thinker to coin this idea. In the second part of the study, which is devoted to a critical reflection on the relationship between religious freedom and religious pluralism in Tertullian’s optic, it becomes clear that when the principle of religious freedom emerged at the end of the 2nd century in North Africa, at least in the case of the Carthaginian teacher, there was no talk of any religious indifferentism. Tertullian makes the greatest Pauline-like concession to other religions in merely recognising that other religions, even if unconsciously, already worship the one true God, the God of the Christians. For Tertullian believes that every human soul is already Christian by nature, but this belief cannot be equated with a principled acceptance of religious pluralism in the sense of indifferentism.